New product development project management practices improvement in a textile company - Fernandes, Adriana (2019)
In today's fierce globalized marketplace, the ability to innovate is one of the prerequisites for excellence to ensure the competitiveness of any organization. The need to respond efficiently and in an integrated manner to the emerging challenges of the daily routines and the need to maintain market leading position encourages the implementation of methodologies that support new product development, making the process of developing new products an important differential. The primary goal of this research was to analyse new product development processes, in order to modify the conventional guidelines and ensure the speed and quality of new products and project management processes in an industrial sewing thread company. This research focused on developing an embryonic solution for the implementation of project management methodologies for the development of new products. As a major contribution, this work presents a reference model that helps the company to plan its product development processes, establish systematic stages for the development process, streamline all the processes involved and thus, increase its chances of success for new products in the market. For that, a new product development project was defined, where adaptations of methods and tools were made according to the latent needs of the organization.